E-Learning of Functioning Principles Medical Intrascopy Systems - Аврунін, О. Г.; Averyanova, L. A.; Golovenko, V. M.; Sklyar, O. (Varna, Bulgaria, 2007)
Principles of E-Learning Medical Intrascopy Systems are described.
Keywords: E-Learning; medical intrascopy; training systems; virtual tomography